The Association Between Knowledge and Parity of Family Planning Acceptors and Interest in Using Female Surgical Method Contraception - Hervina Winerti; Rauza Sukma Rita; Miranie Safaringga; Asih Dewi Setyawati (poltekkes kemenkes mataram, 2023)
Female surgical contraception is a secure and effective means of preventing pregnancy. On the other hand, Indragiri Hulu Regency had the fifth-lowest adoption rate of female surgical method contraception in Riau province in 2019 at 0.7% of all active birth control acceptors. The purpose of this study is to find out the association of knowledge and parity of family planning acceptors with interest in the use of female surgical method contraception in the working area of Air Molek Public Health Center, Indragiri Hulu Regency. This research is a quantitative study with a cross-sectional design conducted in the working area of Air Molek Public Health Center, Indragiri Hulu Regency, from February to October 2021. The sample in this study was an active family planning acceptor in the working area of Air Molek Public Health Center of Indragiri Hulu Regency as many as 92 respondents. The sample was taken with systematic random sampling techniques. Data analysis using chi-square analysis (p≤0.05). The results showed that 33 people (35.9%) had high interest, 30 people (32.6%) had moderate interest, and 29 people (31.5%) had low interest. There is an association of knowledge of KB acceptors with interests (p=0.036) and acceptor parity with interest (p=0.001).